PELATIHAN PENGOLAHAN BATU ALAM BAGI KELUARGA MISKIN DAERAH ALIRAN SUNGAI (DAS) SOOKA, DESA SOOKA, KECAMATAN PUNUNG, KABUPATEN PACITAN, JAWA TIMUR - S Sutriyanto; Bening Tri Swasono (Institut Seni Indonesia Surakarta, 2019)
The background of this training activity is the phenomenon of booming natural stone / akik only enjoyed for some people only, not for the seekers of the stone itself most of the low income people, its role is very vital, because the proximity of natural stone products / akik depends from the Supply they. The fact that the selling price of the raw stone is at least about the same as the selling price of rice, which is ten thousand rupiah per kilo, the selling price of the thumbprints in the exhibition cost hundreds of thousands. This long distance away because the hard work of the stone seekers is not free. We feel the need for skill training to improve their lives. Beginning with providing online marketing insights and account creation training as a facility to sell their products. Increased capacity of knowledge and skills of precious stone production and how to increase trade capacity into bargaining position to make changes in bargaining power in the precious stone trade chain. It is expected from the devotion that we can change their position to the priceless price position of precious stones in the market, because they are the first hands to find these stones and can appear on the market. Through exploration in accordance with the needs in the market will certainly change from the stone. Similarly, this training can at least change their standard of living into citizens who are above the prosperous line.Keywords: processing, natural stone, online marketing, Pacitan.Â